Patterns of child and adolescent psychiatric disorders and associated factors in outpatients attending child psychiatry clinic: a hospital based study - Landge, Anisha P.; Kaur, Darpan; Ghildiyal, Rakesh P. (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood mental disorders are common and yet only a minority of children with mental health problems receive appropriate child mental health consultation. There is scarcity of literature on patterns of child and adolescent psychiatric disorders from developing countries like India. Methods: It was a cross sectional survey on outpatients attending the Child and Adolescent psychiatry clinic, Department of Psychiatry, MGM Medical College, Navi Mumbai. Study sample consisted of all new child & adolescent cases attending the clinic and willing to give consent. Data was analysed for sex, residence, informant, socio-economic status, birth history, family history, medical co-morbidity, reason and source of referral, presence of stressors, psychiatric diagnosis etc using SPSS 20. Institutional Ethics clearance was obtained. Results: Data analysis of n= 150 patients revealed mean age of 9.53 with SD of 3.84. Majority of the patients belonged to school going age group (59.3%), male sex (54.7%), living in urban areas (68.7%), belonging to middle class (56%) and accompanied by mother (54%). 28% had significant birth history while 18.7% had family history of psychiatric illness. 28.7% had co-morbid medical illness. The most common reason for referral was academic problems (24%) from the department of paediatrics (34%). The majority of the cases were diagnosed with ADHD (26%), mental retardation (13.3%), Learning disability (10.7%) followed by Autism (8.0%) & Depression (6.7%). Conclusions:We conclude that there are distinct patterns of child and adolescent psychiatric disorders in our study. Further collaborative research in the arena of child and adolescent mental health is recommended.